Analysis of Root Causes of Fire in Coal Fired Power Plant Using FMEA Study Case Method at PT. PJB UBJOM PACITAN - Muchamad Jati Nugroho; M. Isa Irawan (Institut Teknologi Sepuluh Nopember, 2020)
Fire is one of the highest risks in using coal as fuel for electricity generation. Coal fires often occur in the area of coal handling facilities and are caused by damage to equipment, accumulation of coal dust that has not been cleaned and burning coal itself. This study aims to find out how the application of the FMEA method for the analysis of the root causes of fires in the Coal Power Plant with a case study of the Pacitan steam power plant uses a quantitative approach to find the root cause for prevention by respondents from PT. PJB UBJOM PACITAN at manager and supervisor level. In applying FMEA, the severity, events, and detection is needed to produce risk level figures which will be used as a step in determining the priorities of the company's mitigation management. Based on this study, 15 types of equipment failures were found in the operational coal handling facility at PT PJB UBJOM PACITAN. By using the FMEA method, 6 types of critical failures can be found that require more attention, namely dust on coal which has the potential to cause self-ignition, self-ignition of coal in the area, hot surface, self- combustion in coal yards and perforated crushing bodies.